STEROIDAL SAPOGENINS 172 PREGNEN 5 OL 3 DIONE 12 20 FROM BOTOGENIN AND NEOBOTOGENIN - MARKER, RE (HOTEL GENOVA, CD. MEXICO, DF, MEX, 1949)
A method is given for the conversion of botogenin and neobotogenin into pregnen-5-ol-3-dione-12,20, which may be desirable as a starting material for the synthesis of cortical-type hormones.
JOURNAL PROCEEDINGS LINNEAN SOCIETY BOTANY
Keywords: STEROIDAL SAPOGENINS. 172., PREGNEN 5 OL 3 DIONE 12 20, BOTOGENIN, NEOBOTOGENIN; QUIMICA; QUIMICA ORGANICA; HIDROCARBUROS AROMATICOS